2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32780
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Cultural Influence on Peer Ratings of Teammates between International and Domestic Students

Abstract: Siqing Wei received bachelor degree in Electrical and Computer Engineering at Purdue University. He is in the dual program to obtain master degree in Electrical and Computer Engineering and Ph.D degree in Engineering Education at Purdue University. After years of experience of serving a peer teacher and a graduate teaching assistant in first year engineering courses, he is now interested in study of the existence, cause and interventions on international engineers' teaming behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, from research findings by our group, we know that the differences are often masked at all-dimension levels so that we need to perform individual dimension analysis to explore the discrepancy [25]. In this case, by performing individual dimension analysis as shown in Table 4, we see various mean differences between ENGR I and ENGR II, with the overall tendency that ENGR II ratings are lower than those in ENGR I, but even those that are significant have a very small effect size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, from research findings by our group, we know that the differences are often masked at all-dimension levels so that we need to perform individual dimension analysis to explore the discrepancy [25]. In this case, by performing individual dimension analysis as shown in Table 4, we see various mean differences between ENGR I and ENGR II, with the overall tendency that ENGR II ratings are lower than those in ENGR I, but even those that are significant have a very small effect size.…”
Section: Discussionmentioning
confidence: 99%
“…The dispersion pattern of across CATME dimensions and individual dimension peer rating data is analyzed using ANOVA with a Bonferroni correction to recognize whether differences among the intervention groups are significant; the convergence of self-ratings and peer-rating is tested by Least Square Means [23]- [25].…”
Section: Statistical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of student team collaboration context, Woods et al (2021) used Sharma's survey instrument on ten personal cultural orientations, expanded from Hofstede et al's (2018) national cultural dimensions, to predict students' reported power distance by their uncertainty avoidance and metrics of country culture. Alternatively, Wei et al (2019) examined the cultural influence on peer ratings of teammates between international and domestic students by considering team members' cultural orientation on individualism based on their internationality. Following Wei et al (2019), we define teams consisting of students born in different countries as multicultural teams, as a more straightforward and fundamental way to investigate international students' teaming experiences in U.S. institutions, given the sole focus of our research question on international students.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Wei et al (2019) examined the cultural influence on peer ratings of teammates between international and domestic students by considering team members' cultural orientation on individualism based on their internationality. Following Wei et al (2019), we define teams consisting of students born in different countries as multicultural teams, as a more straightforward and fundamental way to investigate international students' teaming experiences in U.S. institutions, given the sole focus of our research question on international students.…”
Section: Introductionmentioning
confidence: 99%